Bacterial outer membrane vesicle-templated biomimetic nanoparticles for synergistic photothermo-immunotherapy. (October 2022) - Qin, Jiaqi; Yang, Tao; Li, Jianye; Zhan, Guiting; Li, Xin; Wei, Zhaohan; Chen, Zhaoxia; Zheng, Wenxia; Chen, Huabing; Yang, Xiangliang; Gan, Lu
Abstract: A critical challenge in photothermal therapy (PTT) remains in establishing systemic antitumor therapeutics against both primary and distant tumors, due to unsatisfactory photothermal conversion efficiency, insufficient tumor accumulation, and limited antitumor immunity of PTT agents. Here, outer membrane vesicles (OMVs) derived from Escherichia coli Nissle 1917 are explored as the nanoreactors to fabricate biomimetic copper sulfide nanoparticles (CuS-OMVs) for systemic photothermo-immunotherapeutic synergy. CuS-OMVs exhibit high photothermal conversion efficacy, good photostability, and considerable tumor targeting capacity, which thus cause apparent hyperthermia and subsequent distinct suppression of tumor cells at tumors upon second near-infrared (NIR-II) light irradiation. The CuS-OMVs-induced cytotoxicity elicits strong immunogenic cell death (ICD) of tumor cells, and facilitates dendritic cell (DC) maturation and consequent CD8 + T cell activation. Moreover, CuS-OMVs themselves are found to behave as immune adjuvants to promote DC maturation, and simultaneously repolarize M2-like tumor-associated macrophages (TAMs) into M1-like phenotype to reshape immunosuppressive tumor microenvironment. CuS-OMVs thus yield potent antitumor efficacies against both primary tumors and untreated distant tumors upon NIR-II light irradiation. This study provides insights into biomimetic nanomaterials for highly efficient photothermo-immunotherapy toward potent cancer therapy. Graphical Abstract: ga1 Highlights: CuS-OMVs are developed for systemic photothermo-immunotherapeutic synergy. CuS-OMVs induces strong antitumor immunity upon NIR-II light irradiation. CuS-OMVs promote DC maturation and repolarize M2-like TAMs into M1 phenotype. CuS-OMVs exhibit strong anticancer activity upon NIR-II light irradiation.